Model Theory of Planned Behavior to Improve Adherence to Treatment and the Quality of Life in Tuberculosis Patients - Made Mahaguna Putra; Ni Putu Wulan Purnama Sari (Jurnal Ners, 2020)
Introduction: Tuberculosis (TB) is a global public health problem and a leading cause of death from infectious diseases. The research objective was to determine the relationship between the theory of planned behavior, adherence and quality of life using the path model.Methods: This study employed a cross-sectional design with 154 tuberculosis patients. The research was conducted in all community health centers in the Buleleng, Bali. Data on subjective norms, attitudes, perceived behavior control, intention, physical and mental HRQoL domains and medical adherence were collected. Data were analyzed using a descriptive and structural equation model feature using structural equation model.Results: Most respondents have attitudes in the positive category and subjective norms in the good category. Perceived behavior is control in the good category, intentions in the good category and physical health in the good category. Almost all respondents have mental health in the good category and are married. All respondents in this study had adherence to treatment. The influence of subjective norms on intentions (p = <0.01), the influence of intentions on adherence (p = <0.01) and the effect of adherence on quality of life (p = <0.01) were found.Conclusion:Subjective norms are the most important part to influence intention. Adequate TB treatment causes HRQoL to improve.